(untitled) - Tan, Jose Ma. Lorenzo (Philippines, 1995)
This edition includes detailed and opinionated listings and essential information on where to stay, eat, drink, dance, surf, trek, kayak and sail plus a brand-new diving section packed with practical advice on world-class dive sites and operators. You’ll find improved in-depth coverage of major destinations such as Boracay and emerging destinations such as Palawan. The guide features informative background on Filipino history, culture, society, music and politics, and comes complete with new maps and plans for every area.
Keywords: Whales,Dolphins,Whale watching; Identification,Identification; Philippines,Philippines,Philippines